2015
DOI: 10.3168/jds.2014-9057
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, distribution, and diversity of Escherichia coli in plants manufacturing goat milk powder in Shaanxi, China

Abstract: The aim of the study was to investigate the prevalence, distribution, and diversity of Escherichia coli in goat-milk-powder plants in Shaanxi, China. Three plants manufacturing goat milk powder in Shaanxi province were visited once for sampling during 2012 and 2013. Samples were taken for isolation of E. coli. Isolates were characterized by antimicrobial susceptibility testing and detection of virulence genes. All isolates were further examined by pulsed-field gel electrophoresis analysis. In total, 53 E. coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…e report of Ombarak et al [31] in Egypt also showed that the prevalence of E. coli strains in various types of dairy products had a range of 21 to 77% and both were higher than our findings. e overall prevalence of E. coli strains in raw milk samples of studies conducted on Switzerland [32], Iran [33], Italy [34], Egypt [35], Turkey [36], China [37], and Spain [38] had ranged between 1% and 27% which were comparable with our reported prevalence rate.…”
Section: Discussionsupporting
confidence: 88%
“…e report of Ombarak et al [31] in Egypt also showed that the prevalence of E. coli strains in various types of dairy products had a range of 21 to 77% and both were higher than our findings. e overall prevalence of E. coli strains in raw milk samples of studies conducted on Switzerland [32], Iran [33], Italy [34], Egypt [35], Turkey [36], China [37], and Spain [38] had ranged between 1% and 27% which were comparable with our reported prevalence rate.…”
Section: Discussionsupporting
confidence: 88%
“…Elhadidy and Mohammed (2012) [ 21 ] revealed that 11.29% of cheese samples were contaminated with the STEC strains which was lower than our findings (34%). Total prevalence of E. coli strains in raw milk and traditional dairy product samples of studies conducted on Switzerland [ 22 ], Iran [ 23 ], Italy [ 24 ], Egypt [ 25 ], Turkey [ 26 ], China [ 27 ], and Spain [ 28 ] had range between 1% to 27% which were lower than our reported prevalence rate.…”
Section: Discussioncontrasting
confidence: 78%
“…Goat milk accounts for about 2.3% of the worldwide milk production (Claeys et al, 2014). Goat milk-based infant formula is becoming increasingly preferred by consumers (Xi et al, 2015) because of its specific composition and high nutritional utilization (Alférez et al, 2001;Haenlein, 2004;Mwenze and Kiplagat, 2011). China is the largest goat breeding and production country in the world (Luo, 2009;Thiruvenkadan, 2012), and Shaanxi province is one of the major living areas for goats in China (Luo, 2009).…”
Section: Introductionmentioning
confidence: 99%